Effects of preharvest fruit bagging on postharvest quality and shelf life of mango cv. Amrapali (Journal of the Bangladesh Agricultural University, 2020)
Fruit fly and other organisms attack during growth and development of mango fruits which causes severe postharvest losses. Therefore, it is necessarily important to explore some technologies to protect fruits and reduce postharvest losses. This experiment was conducted in order to study the effects of preharvest fruit bagging on the postharvest quality and shelf life of mango cv. Amrapali.  Five bagging materials viz., i) non-bag, control, ii) brown paper, iii) white paper, iv) white polythene and v) black polythene bag were used in this study. The single factor experiment was laid out in randomized complete block design with three replicates. Significant variations were noticed among the preharvest bagging materials in relation to physio-chemical quality attributes and shelf life of mango cv. Amrapali. The attributes such as weight and size of fruits, skin color, moisture, dry matter, vitamin C, sugar (reducing, non-reducing and total), total soluble solids (TSS) contents and shelf life were significantly influenced by the bagging materials. A significant difference was observed in the shelf life of bagged and non-bagged fruits. The longest shelf life (15 days) was found in brown paper bagged whereas the shortest shelf life (8 days) was in non-bagged control fruits. Considering the findings it was observed that brown and white paper bagged fruits appeared to be the superior in respect of skin color, moisture, dry matter, vitamin C, TSS, titratable acidity and extending shelf life in mango cv. Amrapali.J Bangladesh Agril Univ 18(1): 61–67, 2020https://doi.org/10.5455/JBAU.94737